Measuring dispositional optimism in student Veterans: An item response theory analysis. Issue 6 (2nd November 2018) - Umucu, Emre; Brooks, Jessica M.; Lee, Beatrice; Iwanaga, Kanako; Wu, Jia-Rung; Chen, Ada; Chan, Fong
ABSTRACT: Background : The psychometric properties of the Life Orientation Test-Revised (LOT-R) have been established among college students, yet psychometric evidence is lacking for a sample of student Veterans in postsecondary education. Aims : The purpose of this study was to evaluate psychometric properties of the LOT-R for the assessment of dispositional optimism in student Veterans by using classical test theory (CTT) in conjunction with item response theory (IRT). Method : A sample of 205 student Veterans were recruited from universities across the United States. Exploratory factor analysis was conducted to test the unidimensionality of the LOT-R. A polychotomous IRT model using graded response model (GRM) was estimated. Reliability and concurrent validity of the LOT-R were tested. Results : CTT in conjunction with IRT validated that the LOT-R is a psychometrically sound unidimensional instrument for assessing the levels of dispositional optimism in student Veterans. The LOT-R was found to be associated with hope, resilience, PERMA, life satisfaction, depression, and anxiety in the theoretically expected directions. The internal consistency reliability coefficient was computed to be .86. Conclusions : Given its reliability and validity and applicability among this specific population, clinicians, educators, and researchers might use the LOT-R to assess and monitor dispositional optimism among student Veterans.